Uang dan ruang yang berkelanjutan dalam pembentukan Badan Usaha Milik Desa (BUMDes) - Andrian Dolfriandra Huruta; Gatot Sasongko (Masyarakat, Kebudayaan dan Politik, 2016)
Money and space were elements that continually contested. This article aimed to described the role of money and space to support development activity, using the case study of Mbatakapidu. “Money” in this article was referred to fund assistance from external parties such as government (central, province or regency), non-governmental organization (NGOs), and internal side such as self-supporting (local resources), while “space” that referred in this article was local institution called BUMDes (Badan Usaha Milik Desa). This research applied qualitative approach by conducting a case study. Data were gathered through in-depth interview to 5 purposively-selected informants. Secondary data from previous research was used as complement to primary data. Researchers also held a focus group discussion to gain more accurate explanation about the phenomena. The case study shows that fund which entered the village was not yet accompanied by the presence of BUMDes, due to the absence of  supporting regulations such as regional regulation (Perda) and village regulation (Perdes) about BUMDes East Sumba regency, especially in Mbatakapidu. BUMDes as an instrument to develop village’s economics must followed by the presence of regulation as a legal basis, driven by local value which guide knowledge, attitude and practice of indigenous people.